Microcassiope minor (Dana, 1852): a description of the first stage zoea (Crustacea: Decapoda: Brachyura: Xanthidae) - CLARK, P.F.; DIONISIO, M.A.; COSTA, A.C. (Mediterranean Marine Science, 2004)
The first stage zoea of Microcassiope minor (Dana, 1852) is described, illustrated and compared with thirteen other known Xanthinae. This comparison suggests that M. minor is closely related to another Atlantic Ocean xanthid, Nanocassiope melanodactyla (A. Milne-Edwards, 1867). Such an affinity may indicate that the genus Nanocassiope Guinot, 1967) is not a homogenous taxon.